Experimental Modelling And Control Of Pneumatic Cylinder For Manufacturing Applications - Wahidon, Amirul Faez (Universiti Sains Malaysia, 2019)
Kuih Loyang is getting famous from time to time for its crunch and sweetness. The demand for the biscuits is getting higher mostly during the festive day. The slow production of the biscuits has become a problem to meet the demand. A semi-automatic machine had been designed to solve the problem of late production. However, the designed machine cannot work as effective as the traditional machine. To design a semi-automatic machine that can work as effective as the traditional machine, the control of a pneumatic cylinder in an exact position is necessary to create the vibration that will shake off the cake from the mold. To create those vibration using a pneumatic cylinder a full study and understanding need to be done. All type of components such as sensor, solenoid valve, pneumatic cylinder, and microcontroller need to be scrutinized to ensure the pneumatic cylinder move according to the target position. To generate vibration that can resembles human work, the piston in the pneumatic cylinder needs to be controlled at a small distance between 5mm to 10mm and moving repeatedly as looping. The control of pneumatic cylinder distance between 5mm to 10mm will be tested at the Kuih Loyang machine. The control of pneumatic cylinder distance is verified.